BeiDou satellites cross-regional communication path assignment model and resource management - Sheng Liu; Di Wu; Lanyong Zhang (International Journal of Distributed Sensor Networks)
Time division inter-satellite communication and ranging link assignment of BeiDou satellites have made important progress; however, there is still the unsolved issue of integrated communication between ground gateway, aircraft, or even ship, and the BeiDou satellites. Therefore, in this study, we develop a path assignment model based on the idea of clustering and Markov chain. The optimal path is determined by the objective function based on the maximum transition probability. The transition probability takes into account the communication environment, congestion status, aircraft mobility, and reduces the complexity of path assignment by hiding the topology in the region. At the same time, due to the limited resources of onboard computing, storage and bandwidth, we also design a resource management strategy based on task urgency, aimed at minimizing the unreasonable allocation index, to enable the readjustment of link application resources. Finally, the performance of the model and the strategy in average link handover times, link reliability, resource allocation fairness, and network quality of service is determined by simulation.